The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.35808/ijeba/659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Professional Skills and Auditor Competence on Audit Quality in Inspectorate Southeast Sulawesi Province

Abstract: The sample was 31 auditors of the Southeast Sulawesi Provincial Inspectorate attained using the saturation sampling method. The data collected using a questionnaire. Finding: Initially, the questionnaire was tested for validity and reliability, and the test results showed that all instruments were valid and reliable. The test assumptions included autocorrelation test, heteroscedasticity test, normality test, and multicollinearity test. Data analysis employed multiple linear analysis methods. Practical Implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
3
0
1
Order By: Relevance
“…Thus, the accountability improves auditor's performance and objectivity of auditors enables them to operate without the influence of another individual. The results in this study are in line with research which state that competence has an influence on audit quality (Akib & La, 2021;Alim et al, 2007;Ardini, 2010;Iryani, 2017;Kartika & Pramuka, 2019;Meidawati & Assidiqi, 2019;Mispiyanti & Wicaksono, 2021;Muslim et al, 2020;Sari & Susanto, 2018;Tjun et al, 2012). However, it is different from the results which states that Auditor's competence has no effect on audit quality whether it directly or indirectly (Kumalasari et al, 2020;Kusumawati & Syamsuddin, 2018).…”
Section: The Effect Of Competence On Audit Qualitysupporting
confidence: 90%
“…Thus, the accountability improves auditor's performance and objectivity of auditors enables them to operate without the influence of another individual. The results in this study are in line with research which state that competence has an influence on audit quality (Akib & La, 2021;Alim et al, 2007;Ardini, 2010;Iryani, 2017;Kartika & Pramuka, 2019;Meidawati & Assidiqi, 2019;Mispiyanti & Wicaksono, 2021;Muslim et al, 2020;Sari & Susanto, 2018;Tjun et al, 2012). However, it is different from the results which states that Auditor's competence has no effect on audit quality whether it directly or indirectly (Kumalasari et al, 2020;Kusumawati & Syamsuddin, 2018).…”
Section: The Effect Of Competence On Audit Qualitysupporting
confidence: 90%
“…Furthermore, the auditor's ability to detect fraud will be higher with the support of professional skepticism (Hermawan et al, 2021). The results of this study are in line with (Akib, 2021). On the other hand, research by Gracia & Kurnia (2021), showed that professional skepticism cannot provide a moderating effect.…”
Section: H3: Whistleblowing Has a Positive Effect On The Auditor's Ab...supporting
confidence: 77%
“…The results showed that Indonesia is the country with the highest number of fraud cases with a total of 36 cases out of a total of 16 countries in the Asia Pacific region (Hermawan et al, 2021). This condition is very worrying, so it needs proper management because the government is the number 1 organization that loses the most (48.5%) due to fraud (Akib, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the auditor's professional skepticism is an important aspect in assessing the reliability of the assertions or evidence obtained, so that in the audit process the auditor has high enough confidence in a statement or evidence obtained and also considers the adequacy and suitability of the evidence obtained in order to determine whether indication of fraud or not Yustina and Gonadi (2019). Research by Dali et al (2021), Ode et al (2020), and Yuniati and Banjarnahor (2019) reveals that professional skepticism can encourage fraud detection.…”
Section: Introductionmentioning
confidence: 99%